2013
DOI: 10.1590/s1984-46702013000100002
|View full text |Cite
|
Sign up to set email alerts
|

Parental care behavior in the Guiana dolphin, Sotalia guianensis (Cetacea: Delphinidae), in Ilha Grande Bay, southeastern Brazil

Abstract: ABSTRACT. Parental care is any form of parental behavior that increases offspring fitness. To the authors' knowledge, this study is the first to analyze the intensity of parental care in the Guiana dolphin, Sotalia guianensis (van Bénéden, 1864). The objectives of this study are as follows: 1) to quantify the degree of parental care in S. guianensis in Ilha Grande Bay, Rio de Janeiro; 2) to investigate the influence of behavioral state and group size on the degree of parental care; and 3) to evaluate the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In the present study, the core area predicted for the Guiana dolphin, between Pico and Cedro islands, is characterized by shallow waters (1.5–7 m deep) with high mean SSTs. These conditions are appropriate for parental care and the learning of coordinated feeding by the juveniles, given that most dolphin groups have a large proportion of calves and juveniles, and spend most of their time feeding in a coordinated manner (Tardin, Espécie, et al, ; Tardin, Especie, Nery, D'Azeredo, & Simão, ; Tardin, Galvão, et al, ). In fact, most of the prey in the study regions, such as the Brazilian sardine, king mackerel, Scomberomorus cavalla , whitemouth croaker, Micropogonias furnieri , smooth weakfish, Cynoscion leiarchus , and mullet (Begossi et al, ; FIPERJ, ), are also found in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the core area predicted for the Guiana dolphin, between Pico and Cedro islands, is characterized by shallow waters (1.5–7 m deep) with high mean SSTs. These conditions are appropriate for parental care and the learning of coordinated feeding by the juveniles, given that most dolphin groups have a large proportion of calves and juveniles, and spend most of their time feeding in a coordinated manner (Tardin, Espécie, et al, ; Tardin, Especie, Nery, D'Azeredo, & Simão, ; Tardin, Galvão, et al, ). In fact, most of the prey in the study regions, such as the Brazilian sardine, king mackerel, Scomberomorus cavalla , whitemouth croaker, Micropogonias furnieri , smooth weakfish, Cynoscion leiarchus , and mullet (Begossi et al, ; FIPERJ, ), are also found in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐systematic routes were followed at a mean velocity of 10 km/h from the port at Tarituba (Figure ). When dolphins were sighted, the boat's speed was reduced to approximately 5 km/h and focal group follows (Mann, ) were conducted at a minimum distance of 50 m according to the protocol of previous studies (Espécie, Tardin, & Simão, ; Tardin, Espécie, Lodi, & Simão, ). Point locations of the dolphin groups were recorded using a GARMIN VISTA CX GPS device.…”
Section: Methodsmentioning
confidence: 99%
“…At the Ilha Grande Bay, LODI (2003) observed 1,754 individuals in 54 groups; calves were present in 89% of the groups and juveniles in 87% (LODI 2003). In a recent study (TARDIN et al 2013a) observed that 94% of the groups have calves and/or juveniles. In the Sepetiba Bay, the population size is approximately 1,269 individuals (FLACH et al 2008), and calves are present in 80% of the groups.…”
Section: Methodsmentioning
confidence: 95%
“…To determine whether the occurrence of dolphin groups changed between the two time series, the G index to standardize the duration of the observation time accumulated during each time series (adapted from Tardin et al, 2013a) was used: Gigoodbreak=normalN/normalngoodbreak×100 where G i is the standardized proportion of the number of groups observed during sampling period i , N is the number of groups observed during sampling period i and n is the minutes of survey effort.…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether the occurrence of dolphin groups changed between the two time series, the G index to standardize the duration of the observation time accumulated during each time series (adapted from Tardin et al, 2013a) was used:…”
Section: Data Analysesmentioning
confidence: 99%